Iranian Cancer Research Outputs: A Scientometric Study - Zahra Foroughi; Ghasem Janbabaei; Reza Alizadeh-Navaei; Akbar Hedayatizadeh-Omran; Mohammad Eslami; Bijan Geraili; Mahmood Moosazadeh; Siavash Moradi (Journal of Mazandaran University of Medical Sciences, 2017)
Background and purpose: The status and role of each country in scientific production in specific fields may indicate the potential and its performance in promoting and improving that particular issue. Cancer is a major health problem in Iran, so this study aimed to investigate the role of scientific production of Iran about cancer.